2005
DOI: 10.1017/s1461145705006280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antidepressant response in clinical trials of transcranial magnetic stimulation

Abstract: Although previous clinical trials have suggested that repetitive transcranial magnetic stimulation (rTMS) has a significant antidepressant effect, the results of these trials are heterogeneous. We hypothesized that individual patients' characteristics might contribute to such heterogeneity. Our aim was to identify predictors of antidepressant response to rTMS. We pooled data from six separate clinical trials conducted independently, which evaluated the effects of rapid rTMS of the left dorsolateral prefrontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
133
11
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(165 citation statements)
references
References 31 publications
19
133
11
2
Order By: Relevance
“…The decreased amygdyala-left rPFC functional connectivity in response to fearful emotion may be related to the hemispheric asymmetry, which has been demonstrated in individuals with MDD. [41][42][43][44] The balance between the right and left hemispheres is very important to adaptive emotion regulation, and hemispheric asymmetry has been observed in normal affective processing of positive and negative emotions. 45,46 Previous studies have indicated that the left PFC activates more during the regulation of negative affect 47 and approach-related positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased amygdyala-left rPFC functional connectivity in response to fearful emotion may be related to the hemispheric asymmetry, which has been demonstrated in individuals with MDD. [41][42][43][44] The balance between the right and left hemispheres is very important to adaptive emotion regulation, and hemispheric asymmetry has been observed in normal affective processing of positive and negative emotions. 45,46 Previous studies have indicated that the left PFC activates more during the regulation of negative affect 47 and approach-related positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…43 Abnormalities in interhemispheric functioning have been reported previously in patients with MDD. [2][3][4][5][6][7][44][45][46] Lesions in the anterior CC have been implicated in emotional dysregu lation 47 and the hemispheric lateralization of prefrontal abnormalities associated with acute depressive episodes. 48 Mechan isms that may underlie the development of abnormalities in anterior genu CC white matter organization are suggested by recent postmortem studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mood and emotion processing in healthy and neuropsychiatric populations suggest processing of negative emotions relies mainly on the right cerebral hemisphere, whereas the left hemisphere is dominant for positive emotion processing. 1 Convergent evidence from investigations involving repetitive transcranial magnetic stimulation (rTMS), [2][3][4] electroenceph alography (EEG) 5,6 and functional magnetic resonance im aging (fMRI) 7 suggest that an imbalance between left and right hemispheric activity may contribute to the patho physio logy of major depressive disorder (MDD). Abnormal ities particularly in the functional balance between the left and right prefrontal cortices are implicated in the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, lesser effects of non-invasive brain stimulation have been observed in the elderly compared to a younger population. 74 Nevertheless, other studies 25 have shown that 1mA stimulation for 20 minutes is able to induce behavioral …”
Section: Tdcs For Cognitionmentioning
confidence: 97%